Thermomechanical Analysis of Biomass Plastic Composite (BPC) - Madu, Solomon Chijioke; Aigbodion, Victor Sunday; Ike-eze, Ikechukwu (UI Scholars Hub, 2024)
High-performance electrical insulation material can be manufactured using biomass plastic composite (BPC), which is a new type of composite material that is either made up of one or a combination of natural plant fibers/particulates, such as bamboo, cellulose fiber, rice husks, or hemp, and thermoplastic granules. In this study, the BPC composite material that was developed comprised polyethylene (PE), rice husk, and oyster shell. The results of the study showed a significant optimal improvement in the morphological, thermodynamic, and mechanical properties during the addition of 20% to 30% biomass particulates (i.e., rice husk and oyster shell). The thermogravimetric analysis, storage modulus, loss modulus, and damping factor (also known as the tangent of delta [tanδ]) values showed that compositions of the BPC material exhibited an increasing optimal thermomechanical stability when the composition of the BPC material was made with an increasing mixture of oyster shell, rice husk, and PE compared with that when only rice husk was added to PE. Similarly, the mechanical property of BPC was enhanced with 30% biomass material (i.e., rice husk and oyster shell) and 70% low-density PE plastics. This result indicated that BPC materials can be highly durable and long-lasting, as they are less prone to cracking or breaking.